Celebrity politics correlates of voting for celebrities in Philippine presidential elections - David, Clarissa C. (Social Science Diliman, 2015)
It is common in the Philippines for celebrities in entertainment, news, and sports to run for public office and win, even with little experience in political life and limited education. The preponderance of celebrities in politics is often identified in the public discourse as a problem with important implications on national policy. This paper examines empirical correlates of voter preference for celebrity Presidential candidates with data from a nationally-representative survey. It finds support for the hypotheses that the likelihood of voting for celebrity candidates for President and Vice President is associated with education, television exposure, and residence in the capital city. The findings are discussed in the context of political knowledge and its role in shaping voter preferences.